Diversity of Beetles (Order: Coleoptera) at R.E.A.C.H Biodiversity Centre Forest, Cameron Highland. - Nurul Ain Sha’ari (2017)
R.E.A.C.H Biodiversity Centre Forest, Cameron Highland is a 16 years old rehabilitated forest that was cleared for agricultural activities. This forest is managed by Regional Environmental Awareness Cameron Highland (R.E.A.C.H). This study was conducted at R.E.A.C.H Biodiversity Centre Forest, Cameron Highland from July 2016 until August 2016. Coleopterans were sampled using four methods which are sheet light trap, yellow pan trap, pitfall trap and manual collection. A total of 34 specimens of Coleopterans comprising 16 species from eight families were assembled in this study. Light trap was the most efficient method in collecting all the sampled specimens. The diversity of Coleopterans at R.E.A.C.H Biodiversity Centre Forest, Cameron Highland was high with H‟=2.51 (Shannon Wiener Diversity Index) and the species richness recorded also high with DMg=4.25 (Margalef‟s Index). The most diverse beetles collected was the scarab beetles (family Scarabaeidae) followed by family Carabidae. Only one species of Coleopteran is diurnal which isThaumastopeus pugnator, known as green flower beetle. Pictorial identification key was constructed to differentiate the family and genera of Order Coleoptera. Coleopterans diversity and species richness at R.E.A.C.H Biodiversity Centre Forest, Cameron Highland are influenced by habitat changes, forest modification and fragmentations. As a conclusion, the diversity and species richness of Coleopterans species were high for a new rehabilitated forest such as R.E.A.C.H Biodiversity Centre Forest, Cameron Highland. Future scientific studies are strongly encouraged to study the diversity of ecosystem at R.E.A.C.H Biodiversity Centre Forest, Cameron Highland.